Deletion of Fanca or Fancd2 dysregulates Treg in mice - Du, Wei (American Society of Hematology, 2014)
Fanconi anemia (FA) is a genetic disorder associated with bone marrow (BM) failure and leukemia. Recent studies demonstrate variable immune defects in FA. However, the cause for FA immunodeficiency is unknown. Here we report that deletion of Fanca or Fancd2 dysregulates the suppressive activity of regulatory T cells (Tregs), shown functionally as exacerbation of graft-vs-host disease (GVHD) in mice. Recipient mice of Fanca(−/−) or Fancd2(−/−) BM chimeras exhibited severe acute GVHD after allogeneic BM transplantation (BMT). T cells from Fanca(−/−) or Fancd2(−/−) mice induced higher GVHD lethality than those from wild-type (WT) littermates. FA Tregs possessed lower proliferative suppression potential compared with WT Tregs, as demonstrated by in vitro proliferation assay and BMT. Analysis of CD25(+)Foxp3(+) Tregs indicated that loss of Fanca or Fancd2 dysregulated Foxp3 target gene expression. Additionally, CD25(+)Foxp3(+) Tregs of Fanca(−/−) or Fancd2(−/−) mice were less efficient in suppressing the production of GVHD-associated inflammatory cytokines. Consistently, aberrant NF-κB activity was observed in infiltrated T cells from FA GVHD mice. Conditional deletion of p65 in FA Tregs decreased GVHD mortality. Our study uncovers an essential role for FA proteins in maintaining Treg homeostasis, possibly explaining, at least in part, the immune deficiency reported in some FA patients.